2018
DOI: 10.1002/2211-5463.12558
|View full text |Cite
|
Sign up to set email alerts
|

Presence of O‐glycosidically linked oligosaccharides in the cell wall mannan of Candida krusei purified with Benanomicin A

Abstract: Cell wall mannan of the pathogenic yeast Candida krusei was prepared using the antibiotic Benanomicin A, which has a lectin‐like function. The chemical structure of this molecule was found to be similar to that of mannan prepared from the same yeast by the conventional method using Fehling reagent. Only a few degradation products were detected when the mannan prepared using Fehling reagent was subjected to alkali treatment (β‐elimination), but multiple α‐1,2‐linked oligosaccharides were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
3
0
4
Order By: Relevance
“…[12][13][14][15] the presence of α-1,2-, α-1,3-, and α-1,6mannose links. [66][67][68] The spectral patterns shown in Figure 5 were similar to those in their studies and consistent with these findings.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationsupporting
confidence: 89%
See 1 more Smart Citation
“…[12][13][14][15] the presence of α-1,2-, α-1,3-, and α-1,6mannose links. [66][67][68] The spectral patterns shown in Figure 5 were similar to those in their studies and consistent with these findings.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationsupporting
confidence: 89%
“…65,66) The structure of C. krusei was also examined by NMR spectroscopy, and major links were characterized as α-1,2-, α-1,3-, and α-1,6mannose links; however, a precise characterization has not yet been conducted. [67][68][69] In the present study, we demonstrated the clear reactivities of MN fractions to Con A and dectin-2, suggesting biochemical and biological similarities in MN fractions between C. albicans and C. krusei.…”
Section: Discussionsupporting
confidence: 52%
“…These findings were strongly supported by Shibata et al, who reported that βmannosyl transferase was only active at approximately 27ºC and neutral pH 57,58,61) . In the present study, we compared the structures of MN fractions using NMR analysis and found that signals assignable to β -mannosyl linkages were detected in various species, including C. albicans, C. dubliniensis, C. glabrata, C. guilliermondii, a n d C. tropicalis 16,27,28,36,37,42,57,58,60,[62][63][64][65] . The higher ratio of βmannosyl linkages may be a negative factor for clinically isolated Candida species; however, the relationship between vasculitis activity and the presence of β -mannosyl linkages currently remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…20 The structural study of the C. krusei N-linked mannans indicated that the outer chain is short and lightly branched with α-1,2-mannose units, 21 which supports our observations and contrasts with the structure of the C. albicans N-linked mannans, where the outer chain is highly branched with α-1,2-mannose units and capped with either α-1,3-mannose or β-1,2-mannose residues. 22 In regard to the C. krusei O-linked mannans, these are oligosaccharides composed of α-1,2-mannose units that can contain from two to four sugar residues, 23 which again contrasts with the O-linked mannans found on the C. albicans surface, that may contain up to seven α-1,2-mannose residues. 24 Like other Candida species, the C. krusei mannans are modified with mannose residues bound via phosphodiester links, named phosphomannan, although the content of this is about the half of the phosphomannan found in the C. albicans cell wall.…”
Section: Biological and Fungal Aspectsmentioning
confidence: 99%